The Price Revolution in the 16th Century: Empirical Results from a Structural Vectorautoregression Model - Peter Bernholz; Peter Kugler (University of Basel, Center of Business and Economics (WWZ), 2007)
This paper provides empirical evidence in favor of the hypothesis that the secular price increase in the 16th century is mainly caused by money supply developments as the discovery of new mines in Latin America. First we review price developments for several European countries over the 16th century in the light of this hypothesis. Second the application of a SVAR model to annual time series of price indexes for Old Castile and Leon and New Castile over the 16th century indicates that not only the trend but also the short to medium variability of price movements in 16th century Spain are dominated by permanent money supply shocks.
Keywords: E31; E58; E65; 330; Price revolution; money demand; money supply; Preisniveau; Geldnachfrage; Geldmenge; VAR-Modell; Schätzung; Welt